Bundle Size Engineering of Single-Walled Carbon Nanotubes on Silica Nanoparticles. (30th May 2017) - Seo, Deok Min; Hahm, Myung Gwan; Kim, Young Lae
Abstract : Small and large single-walled carbon nanotubes (SWCNTs) bundles from different-sized cobalt catalyst clusters have been synthesized and prepared through chemical vapor deposition (CVD) method by using Co-acetate ethanol solution with silica nanoparticles. By controlling concentration of Co-acetate ethanol solution (0.2 wt% and 0.4 wt%), various sizes and types of bundle of SWCNTs are grown on the silica nanoparticle substrates. Synthesized SWCNT's diameter ranged from 0.92 nm to 1.63 nm, and chirality of SWCNTs and their electronic property from high concentration solution show diverse characteristics. In high concentration solution, the large number of cobalt clusters is induced to merge on the surface of silica nanoparticles and then lots of nucleation points are provided by cobalt clusters for growth of SWNTs. These results give us a promising path to selectively synthesize various types of SWCNTs with different shapes of merged cobalt catalyst. Engineering bundle sizes of SWCNTs can be promising key for diverse applications of carbon nanotubes.